Computer mathematics systems in teaching process - Turskienė, Sigita (Lietuvos matematikos rinkinys, 2002)
The paper analyses possibilities of using computer mathematics systems in teaching process. The work surveys possibilities of using systems by teachers. The advantages and disadvantages of such computer mathematics systems as MAPLE, MATHEMATICA, MATLAB and MATHCAD are also examined in the work.